2020
DOI: 10.3389/fmars.2019.00776
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Competition in the Subpolar Southern Ocean: An Fe–C Co-limitation Experiment

Abstract: Iron (Fe) is a paradox in the modern ocean -it is central to many life-critical enzymes but is scarce across most surface waters. The high cellular demand and low bioavailability of Fe likely puts selective pressure on marine microorganisms. Previous observations suggest that heterotrophic bacteria are outcompeted by small diatoms for Fe supply in the subantarctic zone of Southern Ocean, thereby challenging the idea of heterotrophic bacteria being more competitive than phytoplankton in the access to this trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 100 publications
(126 reference statements)
6
46
0
Order By: Relevance
“…The low rates of primary production and large‐scale upwelling of deep water containing low dissolved organic carbon (DOC) concentrations lead to some of the lowest surface DOC concentrations in the global ocean (∼40–50 µM, Hansell et al., 2012). While low surface dissolved Fe and DOC is thought to restrict heterotrophic bacterial (hereafter bacteria) growth in the Southern Ocean (Church et al., 2000; Obernosterer et al., 2015), studies from Fe‐limited regions have demonstrated that bacteria may also be significant consumers of dissolved Fe and can exhibit greater cellular Fe quotas than phytoplankton (Boyd et al., 2012; Fourquez et al., 2015, 2020; Tortell et al., 1996, 1999). High bacterial Fe demand and uptake rates compared to phytoplankton suggest that bacteria could be significant competitors for dissolved Fe in the Southern Ocean (Fourquez et al., 2015, 2020; Mazzotta et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The low rates of primary production and large‐scale upwelling of deep water containing low dissolved organic carbon (DOC) concentrations lead to some of the lowest surface DOC concentrations in the global ocean (∼40–50 µM, Hansell et al., 2012). While low surface dissolved Fe and DOC is thought to restrict heterotrophic bacterial (hereafter bacteria) growth in the Southern Ocean (Church et al., 2000; Obernosterer et al., 2015), studies from Fe‐limited regions have demonstrated that bacteria may also be significant consumers of dissolved Fe and can exhibit greater cellular Fe quotas than phytoplankton (Boyd et al., 2012; Fourquez et al., 2015, 2020; Tortell et al., 1996, 1999). High bacterial Fe demand and uptake rates compared to phytoplankton suggest that bacteria could be significant competitors for dissolved Fe in the Southern Ocean (Fourquez et al., 2015, 2020; Mazzotta et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this region, the relationships between bacterial production, primary production, C and Fe availability are dynamic and closely intertwined. In the SO, C, and Fe have been reported as being co-limiting for heterotrophic bacteria [ 9 , 13 ], with fierce competition between phytoplankton and bacteria for Fe acquisition. Moreover, such complex relationships can be affected by DOC produced by phytoplankton, which may enhance nutrient availability and bacterial growth (e.g., [ 46 ]).…”
Section: Discussionmentioning
confidence: 99%
“…At the Drake Passage (Bio 1 and 3), PLP concentrations and biodiversity were significantly influenced by C amendments with the largest impact seen with EPS amendment (L 22 and L 6, ), leading to increased PLP abundances and a concomitant decrease in their diversity ( Figure 5 ). Hence, the addition of EPS served as a key driver for heterotrophic bacteria ( Figure 8 ), likely relieving C limitation (e.g., [ 9 ]) in a subset of heterotrophic bacterial populations enabling them to outcompete the other bacterial populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations